BoSapient®, a Cell-Based BoNT-A Potency Assay Optimized for Manual and Semi-Automated Procedures - F. Mark Dunning; Sara Hendrickson; Serena Wolfe; Dan Harding; Theresa Geurs; Timothy M. Piazza; Thomas A. Little; Ward C. Tucker (Toxicon, 2026)

Wettability and sp2/sp3 ratio effects on supercapacitor performance of N-doped hydrogenated amorphous carbon nanofoam - Subrata Ghosh; Giacomo Pagani; Andrea Macrelli; Alberto Calloni; Gianlorenzo Bussetti; Andrea Lucotti; Matteo Tommasini; Raffaella Suriano; Marco Agozzino; Giorgio Divitini; Yurii P. Ivanov; Veronica Piazza; et al. (Chemical Engineering Journal, 2025)

Hyperspectral characterization of wastewater in the Tijuana River Estuary using laboratory, field, and EMIT satellite spectroscopy - Eva Scrivner; Natalie Mladenov; Trent Biggs; Alexandra Grant; Elise Piazza; Stephany Garcia; Christine M. Lee; Christiana Ade; Nick Tufillaro; Philipp Grötsch; Omar Zurita; Benjamin Holt; et al. (Science of The Total Environment, 2025)

Diverse ecological responses of foraminifera to the Middle Eocene Climatic Optimum (MECO) in shallow-water settings (Provençal Domain, NW Italy) - A. Gandolfi; V.M. Giraldo-Gómez; L. Arena; V. Luciani; C.A. Papazzoni; J. Pignatti; M. Piazza; L. Kocsis; C. Baumgartner; A. Briguglio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Loss-of-heat-sink transient simulation with RELAP5/Mod3.3 code for the ATHENA facility - T. Del Moro; F. Giannetti; P. Cioli Puviani; I. Di Piazza; D. Diamanti; M. Tarantino (Annals of Nuclear Energy, 2025)

Comparative analysis of bacterial and microalgal natural astaxanthin: Part I — Focus on composition, molecular interactions, antioxidant activities, physicochemical and biological functions - Cassamo U. Mussagy; Angie V. Caicedo-Paz; Fabiane O. Farias; Alessia Tropea; Roberta La Tella; Juan M. Guzmán-Flores; Luigi Mondello; Rondinelli D. Herculano; Paulo E.L.L. Filho; Rodolfo D. Piazza; Rodrigo F.C. Marques; Daniele Giuffrida; et al. (Algal Research, 2025)

The efficacy of cognitive stimulation, cognitive training, and cognitive rehabilitation for people living with dementia: a systematic review and meta-analysis - Alice Paggetti; Ylenia Druda; Francesco Sciancalepore; Francesco Della Gatta; Antonio Ancidoni; Nicoletta Locuratolo; Paola Piscopo; Luca Vignatelli; Luciano Sagliocca; Antonio Guaita; Piero Secreto; Andrea Stracciari; et al. (GeroScience, 2024)
Cognition-oriented treatments (COTs) are a group of non-pharmacological treatments aimed at maintaining or improving cognitive functioning. Specific recommendations on the use of these interventions in people living with dementia (PLwD) are included in the Italian Guideline on the Diagnosis and Treatment of Dementia and Mild Cognitive Impairment, developed by the Italian National Institute of Health. This systematic review and meta-analysis, based on the GRADE methodology, is part of the guideline. Considered outcomes included the cognitive functions, quality of life, and functional abilities of PLwD, taking into account disease severity, modality and system of delivery, and form of the intervention. The effectiveness of these interventions on caregivers’ outcomes was also assessed. Both group and individual cognitive stimulation were reported as effective in supporting cognitive functions in PLwD at any degree of severity. Individual cognitive training and group cognitive training were reported as effective in improving global cognitive functions in people with mild dementia. Cognitive rehabilitation appeared to be effective only in improving the functional abilities of people with mild dementia. Cognitive rehabilitation appeared to be the most effective in improving caregivers’ outcomes, with results suggesting a reduction in care burden. The observed differences in the effectiveness of these interventions in people with different disease severity can be explained by the intrinsic characteristics of each intervention. Despite the large number of available studies, a high clinical, statistical, and methodological heterogeneity was observed. More methodologically rigorous studies are needed to clarify the effectiveness of each protocol and modality of intervention.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P19-36 Dietary exposure assessment to plasticisers migrating from food contact materials - C. Cascio; G. Bubnyte; F.R. Mancini; M.D.F. Tavares Poças; R. Franz; E. Fabjan; S. Frattini; N. Hellsten; E. Stojanova; K. Baert; M. Georgiadis; G. Di Piazza; et al. (Toxicology Letters, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Biochemical and molecular biomarkers and their association with anthropogenic chemicals in wintering Manx shearwaters (Puffinus puffinus) - Patricia P. Serafini; Bárbara P.H. Righetti; Ralph E.T. Vanstreels; Leandro Bugoni; Clei E. Piazza; Daína Lima; Jacó J. Mattos; Cristiane K.M. Kolesnikovas; Alice Pereira; Marcelo Maraschin; Isadora Piccinin; Tim Guilford; et al. (Marine Pollution Bulletin, 2024)

A Paleogene mixed carbonate-siliciclastic system in the western Tethys: spectral gamma-ray as a tool for the reconstruction of paleoclimate and transgressive-regressive cycles - Victor M. Giraldo-Gómez; Michele Piazza; Luca Arena; Andrea Baucon; Antonella Gandolfi; Cesare A. Papazzoni; Johannes Pignatti; Antonino Briguglio (Marine and Petroleum Geology, 2024)

Short-term middle Eocene (Bartonian) paleoenvironmental changes in the sedimentary succession of Olivetta San Michele (NW Italy): the response of shallow-water biota to climate in NW Tethys - Luca Arena; Victor M. Giraldo-Gómez; Andrea Baucon; Michele Piazza; Cesare A. Papazzoni; Johannes Pignatti; Antonella Gandolfi; Antonino Briguglio (Facies, 2024)
This study focuses on the paleontological content of the middle Eocene (Bartonian) carbonate–siliciclastic sediments of the Capo Mortola Calcarenite Formation from Olivetta San Michele (Liguria, Italy). Along the succession, there are significant paleoecological changes triggered by the variation in neritic input as a consequence of tectonic and climatic instability. Among microfossils, nummulitids prevail, followed by orthophragmines, smaller benthic, and planktonic foraminifera, whereas mollusks and ichnofossils are the most abundant macrofossils. The sudden changes in the benthic communities due to the progressive increase in fluvial input are recorded throughout the sedimentary succession. An increase in water turbidity caused stressful conditions for autotrophic taxa, reducing their size and abundance. In contrast, filter feeders became dominant, suggesting an increase in dissolved and suspended nutrients. Ichnological analysis shows environmental fluctuations controlled by the transport of neritic material offshore, thus confirming the general deepening trend of the studied succession. In the upper part of the succession, we recorded an alternation between gravity flows and marly sediments that are interpreted as short-term alternations between low and intense precipitations. The gravity flows yield taxa such as larger benthic foraminifera (LBF), smaller benthic and planktonic foraminifera, mollusks, and corals. In turn, marls display only a few LBF and abundant smaller benthic and planktonic foraminifera. In these intervals, the increase in planktonic foraminifera also suggests a deepening of the carbonate ramp coinciding with a reduction of light that did not favor the development of LBF. These changes are probably related to the climatic dynamics that occurred in the Bartonian in the western Tethys.

Development of Cell-Based Relative Potency Assays for Antibody-Based Therapeutic Drug Products Against Botulism - Timothy M. Piazza; Theresa L. Geurs; Serena K. Wolfe; Daniel Harding; Thomas A. Little; Ward C. Tucker (Toxicon, 2024)

Sensitive and Accurate Detection of Botulinum Neurotoxin Types A, B, E, and F From Diverse Food Samples Using the BoLISA® Assay - F. Mark Dunning; Timothy M. Piazza; Ward C. Tucker (Toxicon, 2024)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Integrative study of the reproductive biology and growth of Acestrorhynchus pantaneiro Menezes, 1992 (Characiformes, Acestrorhynchidae) - Yanina G. Piazza; Ismael E. Lozano; Sabina Llamazares Vegh; Fabiana L. Lo Nostro; Carlos M. Fuentes (Journal of Fish Biology, 2023)
We studied the reproductive strategy, sexual system and growth of dientudo paraguayo Acestrorhynchus pantaneiro . After 2 years of monitoring in shallow areas of a floodplain lake from the lower Paraná basin (Argentina), it was evidenced that water temperature modulated gonadal maturation, but it was the river water level the synchronising stimulus that triggered spawning. This species exhibited a single annual breeding period from October to January, with most spawning activity in November. According to the von Bertalanffy growth curve, fish would reach autumn to winter months with L S of ~120 mm, already mature males. The first mature females were found at L S of 210 mm, becoming sexually mature between the second and third breeding seasons. This is the first integrative study that includes the body‐length frequency distribution and sex differential size at first maturity and growth, and reports the presence of intersex gonads questioning its sexual pattern from gonochoristic to sequential hermaphrodite species. The sexual pattern, the multiple spawning behaviour and a medium to high absolute fecundity support the opportunistic and invasive behavior observed in previous contributions for this characiform species.

Craniectomies for Dogs With Skull Multilobular Osteochondrosarcoma Using the Misonix Bone Scalpel: Cadaveric Evaluation and Retrospective Case Series - Alexander M. Piazza; Jonathan F. McAnulty; Peter Early; Julien Guevar (Topics in Companion Animal Medicine, 2023)

Role of the YehD fimbriae in the virulence‐associated properties of enteroaggregative Escherichia coli - Jorge Soria‐Bustos; Waleska Saitz; Abraham Medrano; Cristina Lara‐Ochoa; Zineb Bennis; Valerio Monteiro‐Neto; Camilla Itapary dos Santos; Josias Rodrigues; Rodrigo T. Hernandes; Jorge A. Yáñez; Javier Torres; Fernando Navarro‐García; et al. (Environmental Microbiology, 2022)
Summary The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I‐V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new Y eh D f imbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD , also present in most E. coli strains. Immuno‐labelling of EAEC strain 042 with anti‐AAF/II and anti‐YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro‐inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17‐2, 042, 55989, C1010, 278‐1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro‐inflammatory cytokines in supernatants of Caco‐2 cells infected with EAEC strains 042 and J7 and their isogenic Δ yehD mutants showed that these mutants were significantly defective in release of IL‐8 and TNF‐α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

Regional climate downscaling over Europe: perspectives from the EURO-CORDEX community - Daniela Jacob; Claas Teichmann; Stefan Sobolowski; Eleni Katragkou; Ivonne Anders; Michal Belda; Rasmus Benestad; Fredrik Boberg; Erasmo Buonomo; Rita M. Cardoso; Ana Casanueva; Ole B. Christensen; et al. (Regional Environmental Change, 2020)
The European CORDEX (EURO-CORDEX) initiative is a large voluntary effort that seeks to advance regional climate and Earth system science in Europe. As part of the World Climate Research Programme (WCRP) - Coordinated Regional Downscaling Experiment (CORDEX), it shares the broader goals of providing a model evaluation and climate projection framework and improving communication with both the General Circulation Model (GCM) and climate data user communities. EURO-CORDEX oversees the design and coordination of ongoing ensembles of regional climate projections of unprecedented size and resolution (0.11° EUR-11 and 0.44° EUR-44 domains). Additionally, the inclusion of empirical-statistical downscaling allows investigation of much larger multi-model ensembles. These complementary approaches provide a foundation for scientific studies within the climate research community and others. The value of the EURO-CORDEX ensemble is shown via numerous peer-reviewed studies and its use in the development of climate services. Evaluations of the EUR-44 and EUR-11 ensembles also show the benefits of higher resolution. However, significant challenges remain. To further advance scientific understanding, two flagship pilot studies (FPS) were initiated. The first investigates local-regional phenomena at convection-permitting scales over central Europe and the Mediterranean in collaboration with the Med-CORDEX community. The second investigates the impacts of land cover changes on European climate across spatial and temporal scales. Over the coming years, the EURO-CORDEX community looks forward to closer collaboration with other communities, new advances, supporting international initiatives such as the IPCC reports, and continuing to provide the basis for research on regional climate impacts and adaptation in Europe.

Episodic recruitment of young Prochilodus lineatus (Valenciennes, 1836) (Characiformes: Prochilodontidae) during high discharge in a floodplain lake of the River Paraná, Argentina - Ismael E. Lozano; Sabina Llamazares Vegh; María I. Gómez; Yanina G. Piazza; Javier L. Salva; Carlos M. Fuentes (Fisheries Management and Ecology, 2019)
Prochilodus lineatus (Val.) is one of the main target species of South American freshwater fisheries. The following null hypotheses regarding juvenile recruitment of P. lineatus were tested: (a) recruitment is not determined by variations in larval abundance and (b) recruitment is not determined by variations in discharge. For this purpose, variations in abundance of larvae in main channel drift and monthly captures of juveniles in a floodplain lake of the River Paraná were examined weekly between 2009 and 2016. Mean annual abundances of larval densities and CPUE of juveniles were correlated with a set of hydrometric variables. A positive correlation was found between the abundance of juveniles with high and persistent flood pulses. By contrast, larval abundance was not correlated with juvenile abundance. Pronounced contrast was found in the recruitment of P. lineatus between years of high and low discharge, which supports the hypothesis that floods are the main determining factor for recruitment of this species.

Discontinuation of non-anti-TNF drugs for rheumatoid arthritis in interventional versus observational studies: a systematic review and meta-analysis - Fernanda S. Tonin; Laiza M. Steimbach; Leticia P. Leonart; Vinicius L. Ferreira; Helena H. Borba; Thais Piazza; Ariane G. Araújo; Fernando Fernandez-Llimos; Roberto Pontarolo; Astrid Wiens (European Journal of Clinical Pharmacology, 2018)

Phenolic compounds (hydroxycinnamic acids, flavan-3-ols, flavonols) profile in fruit of Italian peach varieties - D. Ceccarelli; A. M. Simeone; P. Nota; M. G. Piazza; C. Fideghelli; E. Caboni (Plant Biosystems, 2016)

Effect of linear alkylbenzene mixtures and sanitary sewage in biochemical and molecular responses in pacific oyster Crassostrea gigas - Fabrício Flores-Nunes; Jacó J. Mattos; Flávia L. Zacchi; Miguel A. S. Serrano; Clei E. Piazza; Silvio T. Sasaki; Satie Taniguchi; Márcia C. Bicego; Cláudio M. R. Melo; Afonso C. D. Bainy (Environmental Science and Pollution Research, 2015)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Exploring the possibility to detect recent temporal changes in highly disturbed sedimentary records through sampling repetitions and core comparisons of porosity and sand content - S. Giuliani; L. G. Bellucci; S. Romano; R. Piazza; C. Turetta; M. Vecchiato; D. H. Nhon; M. Frignani (Environmental Monitoring and Assessment, 2015)

Geomechanical characterization of a highly heterogeneous flysch rock mass by means of the GSI method - G. Pepe; M. Piazza; A. Cevasco (Bulletin of Engineering Geology and the Environment, 2015)

Ecology and diversity of Cortinarius species (Agaricales, Basidiomycota) associated with Quercus ilex L. in the Mediterranean area of Liguria (North-western Italy) - M. Zotti; E. Ambrosio; S. Di Piazza; A. Bidaud; F. Boccardo; M. Pavarino; M. G. Mariotti; A. Vizzini (Plant Biosystems, 2014)

Macrofungi as ecosystem resources: Conservation versus exploitation - M. Zotti; A. M. Persiani; E. Ambrosio; A. Vizzini; G. Venturella; D. Donnini; P. Angelini; S. Di Piazza; M. Pavarino; D. Lunghini; R. Venanzoni; E. Polemis; et al. (Plant Biosystems, 2013)

Wild and cultivated mushrooms as a model of sustainable development - D. Donnini; M. L. Gargano; C. Perini; E. Savino; C. Murat; S. Di Piazza; E. Altobelli; E. Salerni; A. Rubini; G. L. Rana; M. Bencivenga; R. Venanzoni; et al. (Plant Biosystems, 2013)

Biodiversity of rock, beach and water fungi in Italy - S. Onofri; A. Anastasi; G. Del Frate; S. Di Piazza; N. Garnero; M. Guglielminetti; D. Isola; L. Panno; C. Ripa; L. Selbmann; G. C. Varese; S. Voyron; et al. (Plant Biosystems, 2011)

Fungal biodiversity and in situ conservation in Italy - G. Venturella; E. Altobelli; A. Bernicchia; S. Di Piazza; D. Donnini; M. L. Gargano; S. P. Gorjòn; V. M. Granito; A. Lantieri; D. Lunghini; A. Montemartini; F. Padovan; et al. (Plant Biosystems, 2011)

Swimming speed alteration of larvae of Balanus Amphitrite as a behavioural end-point for laboratory toxicological bioassays - M. Faimali; F. Garaventa; V. Piazza; G. Greco; C. Corrà; F. Magillo; M. Pittore; E. Giacco; L. Gallus; C. Falugi; G. Tagliafierro (Marine Biology, 2006)

A new photodegradable molecule as a low impact ballast water biocide: efficacy screening on marine organisms from different trophic levels - M. Faimali; F. Garaventa; E. Chelossi; V. Piazza; O.D. Saracino; F. Rubino; G.L. Mariottini; L. Pane (Marine Biology, 2006)

Relationships between individual sensitivity to CS- and cocaine-induced reinstatement in the rat - V. Deroche-Gamonet; A. Martinez; M. Le Moal; P. V. Piazza (Psychopharmacology, 2003)

X-ray absorption near-edge spectroscopy of transferrins: a theoretical and experimental probe of the metal site local structure - F. Boffi; I. Ascone; S. Della Longa; M. Girasole; G. Yalovega; A. V. Soldatov; A. Varoli-Piazza; A. Congiu Castellano (European Biophysics Journal, 2003)

Study of the addictive potential of modafinil in naive and cocaine-experienced rats - Deroche-Gamonet V.; Darnaudéry M.; Bruins-Slot L.; Piat F.; M. Le Moal; Piazza P. (Psychopharmacology, 2002)

Cryptococcus neoformans Infection in a Cohort of Italian AIDS Patients: Natural History, Early Prognostic Parameters, and Autopsy Findings - S. Antinori; L. Galimberti; C. Magni; A. Casella; L. Vago; F. Mainini; M. Piazza; M. Nebuloni; M. Fasan; C. Bonaccorso; G. Vigevani; A. Cargnel; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

SR141716, a CB1 receptor antagonist, decreases the sensitivity to the reinforcing effects of electrical brain stimulation in rats - V. Deroche-Gamonet; M. Le Moal; P. Piazza; P. Soubrié (Psychopharmacology, 2001)

Comparative XANES study of serotransferrin and ovotransferrin at Cu K-edge: evidence of interactions among the metal sites - F. Boffi; I. Ascone; A. Varoli Piazza; M. Girasole; S. Della Longa; A. Giovannelli; A. Congiu Castellano (BioMetals, 2000)

Cyclin-dependent kinase-like proteins in pea nuclei: their presence and role in cell proliferation - S. Citterio; S. Sgorbati; E. Onelli; M. Gatti; E. Piazza (Protoplasma, 1997)

The fate of murine hepatitis virus (MHV-3) after intravenous injection into susceptible mice - M. Piazza; G. Pane; F. Ritis (Archives of Virology, 1967)